2021
DOI: 10.29227/im-2021-01-17
|View full text |Cite
|
Sign up to set email alerts
|

A Study of PM 10, PM 2.5 Concentrations in the Atmospheric Air in Kraków, Poland

Abstract: The air in Kraków is one of the most polluted in Europe. Polish standards for notification and alert levels for PM10 particulate matterare one of the the highest in Europe and exceed the recommendations of the World Health Organization (WHO) for safe daily concentrations by several times. The article presents the results of airborne dust measurements in three districts of Kraków. The study hasshown that the concentration of PM2.5 and PM10 particulate matter exceeded the annual average permissible levels. Empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Despite the fact that a total ban on burning coal, wood, and other solid fuels in boiler houses, stoves, and fireplaces was imposed in the city of Kraków on September 1st, 2019 [36], in 2019, the number of days when the daily air pollution levels exceeded the 24 h guidelines set by the WHO in 2005 was still very high: 103 d with PM 2.5 > 25 µg m −3 ; 62 d with PM 10 levels > 50 µg m −3 (figure 2). We have also observed that during the year 2020, the first year after the ban to use solid fuels entered into force, the number of days that exceeded the 24 h guidelines values was 94 for PM 2.5 and 56 for PM 10 .…”
Section: Trends In Air Qualitymentioning
confidence: 65%
See 3 more Smart Citations
“…Despite the fact that a total ban on burning coal, wood, and other solid fuels in boiler houses, stoves, and fireplaces was imposed in the city of Kraków on September 1st, 2019 [36], in 2019, the number of days when the daily air pollution levels exceeded the 24 h guidelines set by the WHO in 2005 was still very high: 103 d with PM 2.5 > 25 µg m −3 ; 62 d with PM 10 levels > 50 µg m −3 (figure 2). We have also observed that during the year 2020, the first year after the ban to use solid fuels entered into force, the number of days that exceeded the 24 h guidelines values was 94 for PM 2.5 and 56 for PM 10 .…”
Section: Trends In Air Qualitymentioning
confidence: 65%
“…In addition to the previous analysis, we have estimated the potential benefits that would have occurred had pollution levels observed in 2019 been reduced to meet the WHO 2015 guidelines (for the long-term effects only). The expected reduction in number of cases is as high as a 30.6% in asthma incident cases for PM 2.5 and 27.4% for PM 10 . In addition, achieving the WHO 2005 guidelines in 2019 would have resulted in a 14.1% lower number of preterm births and 10.2% fewer cases of low birth weight (table 5).…”
Section: September 2017 National Emission Requirements For Solid Fuel...mentioning
confidence: 94%
See 2 more Smart Citations
“…A particularly important aspect of appying geometrization of iron ore deposits is geometrical prediction of their quality indicators for solving tasks of current and long-term planning in order to provide the most efficient performance of the mining enterprise in terms of ore blending and to improve rationalization of deposit development. It is also of great importance to carry out mining operations with the minimal impact on the environment and the rock massif [27][28][29][30]. This can be achieved based on a clear understanding of rock properties and geological indicator distribution in the massif.…”
Section: Introductionmentioning
confidence: 99%